Comparison of Antidiabetic Medications during the Treatment of Atherosclerosis in T2DM Patients - Xiaojie Liu; Tao Mei; Wei Chen; Shandong Ye (Hindawi Limited, 2017)
Type 2 diabetes is often associated with arterial atherosclerosis in large blood vessels. We set out to elucidate whether commonly used antidiabetic drugs metformin, sitagliptin, and pioglitazone will reduce atherosclerosis in T2DM patients. We enrolled 176 individuals with type 2 diabetes, which were divided into four treatment groups according to different oral drugs: metformin alone, sitagliptin alone, pioglitazone alone, or combination of metformin and sitagliptin. We assessed changes in glycometabolism, lipid metabolism, cytokine released, and carotid artery intima-media thickness as the readout for improvement in atherosclerosis. HbA1c levels were significantly decreased in all treatment groups (p<0.05), and FBG levels were also decreased in metformin and combined groups (p<0.05). In addition, we found IL-6 levels significantly decreased in all treatment groups (p<0.05). Treatment with pioglitazone showed a significant increase in BMI, HDL, and ADPN levels (p<0.05). We also observed a significant decrease in NHDL levels in the combined treatment group (p<0.05). Our data revealed that in addition to hypoglycemic properties of metformin, sitagliptin, and pioglitazone, these drugs also have the potential to promote an anti-inflammatory response. Therefore, combination therapy may be more beneficial for reducing atherosclerosis in patients with type 2 diabetes. The clinical trial is registered with ChiCTR-ORC-17010835.